Enhancing Middle School Mathematics Teaching Effectiveness through the Utilization of GeoGebra Software - Zhao, Daying; Chen, Lina; Fu, Chan Liu (Advances in Social Sciences Research Journal, 2024)
With the widespread application of modern information technology in the field of education and the deepening of the new curriculum reform, middle school mathematics teaching is facing new opportunities and challenges. As a powerful dynamic mathematics software, GeoGebra plays an increasingly important role in middle school mathematics teaching due to its intuitiveness, interactivity, and dynamism. This paper first introduces the characteristics of GeoGebra software and then elaborates on its application in middle school mathematics teaching from the perspectives of teachers and students, aiming to provide new ideas and methods for mathematics teaching.